Investigating deep earthquake mechanisms of the M6.6 Java Sea earthquake, 2016 - Fang, Shiyuan (2019)
Devastating earthquakes in the brittle shallow earth occur due to frictional sliding between the plates. However, at the depth between 100 and 600km, where brittle deformation is inaccessible, deep earthquakes occur frequently. Therefore, deep earthquakes require a different mechanism. The M6.6 Java Sea Earthquake in October 2016 has a depth of more than 600 km. We downloaded broadband waveform data of this earthquake from 289 stations around the world from the Incorporated Research Institution for Seismology (IRIS). In this project, we obtained focal mechanism of the earthquake using the Cut-And-Paste method (Zhu and Helmberger, 1996, BSSA). We obtained the source depth for the earthquake by fitting synthetic waveforms with the actual waveforms, using the sP-wave arrival time as an indicator for the depth. We finetuned the focal mechanism using the depth. With the new focal mechanism, we obtained the source duration in each station by comparing the P-wave signal. Finally, we plotted the source duration against the station azimuth, and compared the scatter graph with a model, to gain understanding on the rupture directivity. Through this project, we obtained source information for the earthquake, including the focal mechanism of the earthquake, the depth, the source duration as well as information about the rupture directivity of the earthquake.